University campuses as small-scale models of cities: Quantitative assessment of a low carbon transition path. (October 2019) - Guerrieri, M.; La Gennusa, M.; Peri, G.; Rizzo, G.; Scaccianoce, G.
Abstract: The energy efficiency interventions and rehabilitation actions regarding university campuses are characterized by an emblematic impact, representing significant examples of good practices that a given community could adopt, even at the city level. Starting from the idea that campuses may be regarded as small scale models of cities, a quantitative method for estimating to which extent the adoption of a given set of interventions by a municipality could contribute to make such city close to a nearly zero energy profile is proposed. To accomplish this task, the study considers the low carbon transition path of the campus of the University of Palermo and applies a simple method that, implementing an idea firstly developed by Yoshida et al. (2017), provides a rapid and effective graphical representation of the level of the success reached by the campus in terms of accomplishment of the nearly zero energy targets. The analysis of the transferability of such method to cities has shown that it can also be easily adopted by a city's administration and can be used for assessing the effectiveness of actions typically belonging to a city's energy policy, such as the public procurement and the waste management, apart from the actions regarding the public transportation system and the energy efficiency of the public building stock. Highlights: University campuses have been shown to be quite a high energy –consuming. The path of the University of Palermo towards a low carbon profile is discussed. The transferability to the city context of the presented method is evaluated. A new concept, namely the nearly zero energy campus (nZEC) is introduced. Achieving EEC through more sustainable mobility habits of commuter students.